2023
DOI: 10.1002/adma.202307942
|View full text |Cite
|
Sign up to set email alerts
|

1D Magnetic MX3 Single‐Chains (M = Cr, V and X = Cl, Br, I)

Yangjin Lee,
Young Woo Choi,
Kihyun Lee
et al.

Abstract: Magnetic materials in reduced dimensions are not only excellent platforms for fundamental studies of magnetism, but they play crucial roles in technological advances. The discovery of intrinsic magnetism in monolayer two‐dimensional van der Waals systems has sparked enormous interest, but the single‐chain limit of one‐dimensional magnetic van der Waals materials has been largely unexplored. Here, we report on a family of one‐dimensional magnetic van der Waals materials with composition MX3 (M = Cr, V, and X = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The influence of guest materials on the electronic structure of SWCNTs and the interpretation of a structure–property relationship between the sub-nanometer 1D heterostructures have become fundamental interests and challenges for researchers. It has been empirically demonstrated that the smallest isolated perovskite structures with a sub-1 nm thickness can remain stable within SWCNTs. Under surface constrained conditions, these structures experience profound alterations in their physical and structural properties .…”
Section: Introductionmentioning
confidence: 99%
“…The influence of guest materials on the electronic structure of SWCNTs and the interpretation of a structure–property relationship between the sub-nanometer 1D heterostructures have become fundamental interests and challenges for researchers. It has been empirically demonstrated that the smallest isolated perovskite structures with a sub-1 nm thickness can remain stable within SWCNTs. Under surface constrained conditions, these structures experience profound alterations in their physical and structural properties .…”
Section: Introductionmentioning
confidence: 99%
“…The use of carbon nanotubes (CNTs) and boron nitride nanotubes (BNNTs) as reaction templates for encapsulation has proven highly effective for synthesizing various nanostructures. This innovative method enables the creation of a diverse array of vdW 1D materials by introducing various substances such as monoelements, perovskites, metal halides, carbides, and chalcogenides into the confined spaces of nanotubes. In particular, the small inner diameter of the nanotubes is advantageous for synthesizing 1D chain structures because it limits the radial growth of the encapsulated material. This geometric confinement effect of nanotubes has provided the opportunity for the emergence of crystal structures and properties not found in their bulk form. Furthermore, the protective sheaths formed by the nanotubes play a crucial role in shielding the encapsulated materials from degradation, thereby facilitating the investigation of various nanostructures.…”
Section: Introductionmentioning
confidence: 99%